(untitled) (Homiletic, 2016)
This essay’s purpose is to explore the radical nature and trajectory of the Du Boisian prophetic tradition. A significant part of this tradition is its metanarrative’s form and function, which is first located in W. E. B. Du Bois’ writings and secondly located in seminal writings and sermons of Martin Luther King Jr. The Du Boisian metanarrative is focused on economic justice, which here is economic reparations.